The consequences of understanding expert probability reporting as a decision. Issue 1 (January 2017) - Biedermann, A.; Bozza, S.; Taroni, F.; Aitken, C.
Abstract: In this paper we reiterate that the personalist interpretation of probability is inevitable and as least as informed as any other allegedly more 'objective' definition of probability. We also argue that the problem faced by forensic scientists, the reporting on imperfect personal knowledge, in terms of probabilities, can be reconstructed as a decision problem. Tackling this problem through a rigorous decision theoretic analysis provides further argument in support of the view that optimal probability reporting is in terms of single numbers, not intervals.